Effect of standardized Eucalyptus globulus leaf extract on brain oxidative stress and aberrant neurochemistry of fructose-streptozotocin-induced diabetic rats (Nigerian Journal of Physiological Sciences, 2023)
The neuro-pharmacological effect of Eucalyptus globulus ethanol leaf extract in fructose-streptozotocin-induced diabetic rats was evaluated in this study. The phytochemical analysis of the extract was carried out using HPLC-DAD. Diabetes was induced in rats with 10% fructose in drinking water and a single intraperitoneal injection of 40 mg/kg streptozotocin (STZ). Diabetic animals were orally treated with 100-400 mg/kg of the extract for 21 days with glibenclamide as the reference drug. Blood and brain tissue were processed for the determination of serum electrolyte levels, hematological indices, and biochemical estimations. Ergosterol, pinitol, catechin, quercetin, robinetinidol, and other polyphenols were identified in the extract. Diabetic animals showed decreased serum potassium and sodium ion levels and decreased hematocrit, hemoglobin, red blood cells, white blood cells and lymphocytes but increased neutrophils. The brains of animals in the untreated diabetic group with increased blood glucose level showed oxidative stress (increased level of MDA and myeloperoxidase but decreased level of reduced glutathione and superoxide dismutase) and disturbed neurochemistry (increased level of acetylcholinesterase and monoamine oxidase but decreased level of Na+K+ATPase, tyrosine hydroxylase and dopamine). Administration of the Eucalyptus globulus leaf extract remarkably ameliorated the observed hyperglycemia, electrolyte, and hematological imbalances in animals. In addition, the administration of the extract attenuated the brain redox imbalance, and neurochemical disturbances in the rats. These results show that Eucalyptus globulus leaves contain antioxidant and neurotransmitter modulating phytochemicals with the potential to be developed as therapeutic agents for the management of diabetic cerebrovascular problems and related complications.